2012
DOI: 10.1002/app.36896
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of modified starch‐grafted poly(lactic acid) and a study on compatibilizing efficacy of the copolymers in poly(lactic acid)/thermoplastic starch blends

Abstract: This study has concerned preparation of polylactic acid grafted with maleated thermoplastic starch (PLA-g-MTPS) and a study on compatibilizing efficacy of the above copolymers in PLA/thermoplastic starch (TPS) blends. The PLA-g-MTPS copolymers were prepared by two-step reaction. First, maleated thermoplastic starch (MTPS) was prepared by reacting cassava starch with glycerol and maleic anhydride (MA). Second, the MTPS was grafted onto PLA molecules using peroxide as an initiator. Chemical structures of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 19 publications
4
50
0
Order By: Relevance
“…A titration method 19 was used to determine the percentage of MA grafted on PLA. A titration method 19 was used to determine the percentage of MA grafted on PLA.…”
Section: Methodsmentioning
confidence: 99%
“…A titration method 19 was used to determine the percentage of MA grafted on PLA. A titration method 19 was used to determine the percentage of MA grafted on PLA.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the difficulties in preparation of specific copolymers such as the compatibilizer. Maleated starch grafted PLA (PLA‐ g ‐MTPS) has been prepared as compatibilizer for a PLA/TPS blend . In the presence of PLA‐ g ‐MTPS copolymer, the PLA/TPS blend morphology was improved by reducing coalescence of the starch phase in PLA matrix.…”
Section: Principle and Mechanism Of Ex Situ Compatibilization Of Polymentioning
confidence: 99%
“…The presence of COOH groups in the m-PEG was evaluated using back titration technique according to Wootthikanokkhan et al (2012).…”
Section: Characterizationmentioning
confidence: 99%
“…Other compatibilizers such as maleic anhydride (MA) Zhang & Sun, 2004), PLA-g-MTPS (Wootthikanokkhan et al, 2012), PLA-g-amylose (Schwach, Six, & Avérous, 2008) have also been reported in literatures.…”
Section: Introductionmentioning
confidence: 99%